Supramolecular encapsulation of hexaaquacobalt(ii) cations in a hydrogen-bonded framework for slow magnetic relaxation and high proton conduction. Issue 48 (28th November 2022) - Shao, Dong; Zhou, Yue; Yang, Xiaodong; Yue, Jing; Ming, Shujun; Wei, Xiao-Qin; Tian, Zhengfang
Abstract : A cobalt-based hydrogen-bonded organic framework (HOF) was reported to show field-induced single-ion magnet (SIM) behavior and high proton conductivity, representing the first example of a proton-conducting SIM-HOF. Abstract : The supramolecular assembly of hexaaquacobalt(ii ) nitrate and a tetradentate carboxylate ligand resulted in the isolation of a cobalt hydrogen-bonded organic framework (HOF). Variable-temperature X-ray diffraction experiments reveal high thermal stability of the framework sustained by charge-assisted, multiple hydrogen bonding interactions with the co-former. Interestingly, the material shows field-induced slow relaxation of magnetization originating from the magnetically anisotropic Co 2+ ions within the supramolecular framework, revealing a rare single-ion magnet (SIM) HOF. Additionally, the HOF also exhibits high proton conductivity above 100 °C due to the extensive H-bond networks and high content of water and carboxylate within the material. More importantly, these results not only observe the magnetic and electrical properties of an old molecule but also demonstrate a significant turn-on effect of multifunctionalities from non-functional synthons achieved in a supramolecular approach.